Are You There God? It's Me, Margaret - Blume, Judy (Englewood Cliffs, N.J., : Bradbury Press, 1970)
Faced with the difficulties of growing up and choosing a religion, a twelve-year-old girl talks over her problems with her own private God.
Keywords: Religions -- Fiction; Adolescence -- Fiction; Adolescent girls -- Fiction; Religion -- Fiction; Girls -- Fiction; New Jersey -- Fiction